Mixed matrix membranes for gas separation : plasticization study on cellulose acetate and zeolite incorporated cellulose acetate MMMs - Tanaporn Tanupabrungsun (Chulalongkorn University, 2014)
Thesis (M.S.) -- Chulalongkorn University, 2007